A cost utility analysis of non-operative management, total wrist arthroplasty, and total wrist fusion in rheumatoid arthritis - Cavaliere, Christi M. (2010)
PURPOSE: Management of end stage rheumatoid wrist disease remains controversial. Total wrist fusion (TWF) provides reliable pain relief and stability and is the most commonly applied management strategy. Total wrist arthroplasty (TWA) is a motion-preserving alternative that is gaining popularity. The purpose of this study is to perform a cost–utility analysis comparing non-operative management, TWA and TWF for the rheumatoid wrist METHODS: A time trade-off utility survey was developed to investigate patient and physician preferences for the potential outcomes of TWA and TWF. The study sample consisted of rheumatoid patients (N=49) recruited as part of an ongoing prospective study as well as a national random sample of hand surgeons and rheumatologists (N=109). A decision tree was created using utility values derived from the survey, and the expected quality-adjusted-life-years (QALYs) for each procedure were determined. Using the societal perspective, costs were based on the Medicare fee schedules for the CPT codes associated with TWA and TWF and their potential complications. Costs per QALY were calculated and compared. RESULTS: Patients and physicians both showed a preference for operative management over non-operative management. Application of cost data indicated that the incremental cost per additional QALY gained for TWA over non-operative management was $2,281 and the incremental cost per QALY gained with TWA over TWF was $2,328 which is substantially less than the national standard of $50,000/QALY deemed acceptable for adoption. CONCLUSIONS: In the absence of rigorous outcome data, cost-utility analysis is a useful tool to guide treatment decisions. TWA and TWF are both extremely cost-effective procedures. This study incorporated patient and physician utilities to demonstrate that TWA has only a small incremental cost over the traditional TWF procedure. Based on this economic model, TWA may be worthy of further consideration and cost should not be considered prohibitive.